علاقة التدفق النفسي بالعنف المدرسي لدى تلاميذ سنة أولى ثانوي - نصرات, الروميصاء; نصرات, مريم (جامعة الوادي university of Eloued, 2022)
الملخص: هدفت الدراسة الحالية إلى معرفة العلاقة بين التدفق النفسي والعنف المدرسي لدى تلاميذ أولى ثانوي, بلغت عينة الدراسة (80) تلميذا وتلميذة من ثانوية لوبيري محمد بالحمادين, وتم استخدام المنهج الوصفي الارتباطي ومقياس التدفق النفسي ومقياس العنف المدرسي واستخدمت الاساليب الاحصائية الاتية: معامل ارتباط بيرسون, واختبار تحليل التباين f للكشف عن دلالة الارتباط بين التدفق النفسي والعنف المدرسي لدى تلاميذ سنة أولى ثانوي, اختبار "ت"Ttest لعينتين مستقلتين. وتوصلت الدراسة الحالية إلى النتائج التالية: - لا توجد علاقة ارتباطية دالة احصائيا في مستوى التدفق النفسي والعنف المدرسي لدى عينة الدراسة. - لا توجد فروق ذات دالة احصائية بين الذكور والإناث من تلاميذ سنة أولى ثانوي تعزى لمتغير الجنس على مقياس التدفق النفسي. - لا توجد فروق دالة احصائيا بين تلاميذ سنة أولى ثانوي على قياس التدفق النفسي تبعا للشعبة الدراسية (علوم/آداب). - لا توجد فروق دالة احصائيا تلاميذ سنة أولى ثانوي على مقياس التدفق النفسي تبعا لحالة المتمدرس( معيد/غير معيد). Abstract: The current study aimed to know the relationship between the psychological flow and school violence of secondary 1st students The research reaches 80 students (male and female) in Lobery Mohammad in Hamaden. Moreover, the descriptive correlative method, psychological flow scale and school violence scale are used. The following statistical methods are used: Pearson correlation coefficient, analysis of variance to reveal the correlation between the psychological flow and school violence of the students of secondary 1st and T test for tow independent samples. The study states: There is no correlative relationship indicating Statistically between the psychological flow and school violence according to what has been concluded. There are no statistical differences between males and females from student of secondary 1st for gender variance at the psychological flow scale There are no statistical differences between 1st secondary students at psychological flow scale according to the arts and sciences section There are no statistical differences 1st secondary students at psychological flow scale according to the status of the lecturer – teaching assistant or not.
مذكرة ماستر علم النفس تخصص علم النفس المدرسي
Keywords: التدفق المدرسي، العنف المدرسي; Flux scolaire, violence à l'école; School flow, school violence